Doctoral Students’ Use of Generative Artificial Intelligence (GenAI) in Academic Writing: Their Engagement with AI-Powered Writing Tools - Li, Vickie W. K.; Lin, Linda H.F. (Discourse and Writing/Rédactologie, 2025)
Since the launch of ChatGPT in 2022, a range of Generative Artificial Intelligence (GenAI) tools have emerged to support students’ English academic writing, benefiting particularly English as an additional language (EAL) students. Previous studies have primarily focused on undergraduates’ knowledge, perceptions, and practices of GenAI use in writing. Research on postgraduates, especially EAL doctoral students’ engagement with GenAI remains relatively limited; yet, these students are expected to demonstrate a higher level of writing proficiency to effectively disseminate their research within the academic community. To address this gap, this study aims to examine how EAL PhD students engage with GenAI tools behaviourally, cognitively, and affectively in a thesis writing course. Data were collected from students through questionnaire surveys and focus group interviews. Findings reveal that most participants viewed GenAI as a valuable tool for assisting their writing. However, some expressed hesitation about using the technology due to concerns about academic reputation and the originality of their research writing. This study has significant pedagogical implications regarding: i) the support needed by EAL PhD students to effectively use GenAI in their writing; and ii) possible ways to integrate GenAI technology into academic writing courses.